Disaster Risk Reduction Based on Community through a Contingency Plan for Mount Sinabung - Puji Lestari; Eko Teguh Paripurno; Arif Rianto Budi Nugroho (Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
The eruption of Mount Sinabung in Karo district of North Sumatera has continued on and oﬀ since 2010. A contingency plan is needed to reduce the risk of disaster. The purpose of this research is to find a disaster communication model in community-based disaster risk management through Sinabung Eruption Contingency Plan of Karo Regency, North Sumatera Province. This research applies the concept and models of community-based disaster management. The research objectives are to make a disaster risk management model based on the community as a contingency plan for Sinabung. A qualitative method is used by the researchers to finish this paper. This research is held in risk area of Mount Sinabung, Karo, Sumatera Selatan. The object of this research is the ability of government, non-government, and also society as actors of concept and models of community-based disaster management communication. The researchers analyze the program and the competency of the actor concept and the models of community-based disaster management communication. The result of this research is a disaster communication model in community- based disaster risk management through Sinabung Eruption Contingency Plan.